Experimental study of convective heat transfer at the surface of a rail due to train passage. (February 2015) - Wang, Mian; Zhang, Yong-Heng; Bai, Jun; Wang, Liang-Bi
Frictional heat is generated when a train wheels pass over the rail. In addition heat is also generated by the use of an eddy current brake system. This generated heat causes a variation in the temperature of a rail's surface; it accelerates the formation of both rolling contact fatigue and wear on the wheel/rail contact surface; and threatens the running safety of railway vehicles. The convective heat transfer characteristics on the surface of a rail when the train passes over it are very important in determining the temperature change of the rail. This paper reports experimental results of the convective heat transfer characteristics on a rail's surface when a rolling wheel passes over the rail. A test model was created based on the configuration commonly used in a two-bogie car. The local and average heat transfer coefficients of the test section of the rail were obtained. The heat transfer results were extended to the real case using an analogy between the frequencies of the test wheel and train wheels. The results show that when the speed is less than 182 km/h, the intensity of convection heat transfer on the rail's surface increases with an increase in the speed of the train, however, it decreases significantly when the speed is larger than 182 km/h.